Full cup test (FCT) for symptom severity assessment in carpal tunnel syndrome/comparing scores with clinical and neurophysiological findings (Annals of Medical Research, 2021)
Aim: Carpal tunnel syndrome (CTS) is a compression neuropathy. There is neuropathic pain in the clinic. Treatment is planned according to electrodiagnostic testing (EDX) and symptom severity. This study was planned to evaluate of full cup test (FCT) to demonstrate symptom severity in CTS and investigate the relationship between FCT and EDX.Material and Methods: This study included patients with idiopathic CTS. The self-administered Boston Carpal Tunnel Syndrome Questionnaire (BCTQ) and FCT were used to determine the severity of clinical symptoms. The severity of CTS was classified as mild, moderate and severe according to EDX. Results: A total of 97 hands (55 right, 42 left) were evaluated. 29 patients had bilateral symptoms. The severity of CTS was 51.5% mild, 44.3% moderate, and 4.1% severe. The mean FCT score was 51.13 ± 20.80 (min: 6.6-max: 100). The mean symptom severity scale (SSS) of the BCTQ was 24.25 ± 7 and the functional severity scale (FSS) was 13.26 ± 4.55. The score of FCT was significantly correlated with SSS and the FSS (r=0.60 p 0.001, r=0.65 p 0.001). Significant correlation was observed between FCT and EDX (r=0.57, p=0.001). Conclusion: FCT can be used to assess the severity of neuropathic pain in CTS and may be a guide in planning treatment.
Keywords: Carpal tunnel; electrodiagnostic test; full cup test; neuropathy; pain